A Tale of Two Peas in a Pod: The Kepler-323 and Kepler-104 Systems - C. Alexander Thomas; Lauren M. Weiss; Howard Isaacson; Hilke E. Schlichting; Corey Beard; Casey L. Brinkman; Ashley Chontos; Paul Dalba; Fei Dai; Steven Giacalone; Jack Lubin; Judah Van Zandt; et al. (The Astronomical Journal, 2024)
In order to understand the relationship between planet multiplicity, mass, and composition, we present newly measured masses of five planets in two planetary systems: Kepler-323 and Kepler-104. We used the HIRES instrument at the W.M. Keck Observatory to collect 79 new radial velocity (RV) measurements for Kepler-323, which we combined with 48 literature RVs from TNG/HARPS-N. We also conducted a reanalysis of the Kepler-104 system, using 44 previously published RV measurements. Kepler-323 b and c have masses of ${2.0}_{-1.1}^{+1.2}$ M _⊕ and 6.5±1.6 M _⊕ , respectively, whereas the three Kepler-104 planets are more massive (10.0±2.8 M _⊕ , ${7.1}_{-3.5}^{+3.8}$ M _⊕ , and ${5.5}_{-3.5}^{+4.6}$ M _⊕ for planets b, c, and d, respectively). The Kepler-104 planets have densities consistent with rocky cores overlaid with gaseous envelopes ( ${4.1}_{-1.1}^{+1.2}$ g cc ^−1 , ${2.9}_{-1.5}^{+1.7}$ g cc ^−1 , and ${1.6}_{-1.1}^{+1.5}$ g cc ^−1 respectively), whereas the Kepler-323 planets are consistent with having rocky compositions ( ${4.5}_{-2.4}^{+2.8}$ g cc ^−1 and ${9.9}_{-2.5}^{+2.7}$ g cc ^−1 ). The Kepler-104 system has among the lowest values for gap complexity ( ${ \mathcal C }$ = 0.004) and mass partitioning ( ${ \mathcal Q }$ = 0.03); whereas, the Kepler-323 planets have a mass partitioning similar to that of the Inner Solar System ( ${ \mathcal Q }$ = 0.28 and ${ \mathcal Q }$ = 0.24, respectively). For both exoplanet systems, the uncertainty in the mass partitioning is affected equally by (1) individual mass errors of the planets and (2) the possible existence of undetected low-mass planets, meaning that both improved mass characterization and improved sensitivity to low-mass planets in these systems would better elucidate the mass distribution among the planets.